Research on current decoupling control of six‐phase permanent magnet linear synchronous motor for electromagnetic launch. Issue 2 (30th December 2021) - Sun, Xingfa; Xu, Jin; Zhu, Junjie
Abstract: Six‐phase permanent magnet linear synchronous motor (PMLSM) for electromagnetic launch (EML) system presents the characteristics of a high order, nonlinearity, multivariable, strong coupling, and nonperiodic transient operation in the synchronous rotating coordinate system, posing a great challenge to the dynamic response ability of the current loop. Existing research on current decoupling control (CDC) mainly focuses on cross decoupling within a three‐phase system,  even though there are neither decoupling methods for multiphase systems nor effective evaluation criteria for the decoupling and dynamic response performances. From this perspective, this paper first presents an equivalent reduced‐order complex‐matrix dynamic mathematical model of six‐phase PMLSM and analyze its transient coupling characteristics during the process of EML. Then, the CDC methods of six‐phase PMLSM based on direct compensation and matrix diagonalization principles are realized, respectively, to accomplish the cross decoupling and back electromotive force decoupling within and between different three‐phase windings. Finally, an all‐round method is proposed, for the first time, to evaluate the decoupling performances and dynamic response performances of different CDC strategies for six‐phase PMLSM. Significant superiority of deviation decoupling regulator in decoupling performance and robustness are verified based on high‐speed EML experimental platform of six‐phase PMLSM.